EVALUATION OF THE SERVICE LEVEL OF THE SIMPANG EMPAT AIR HITAM WITHOUT FLY OVER IN SAMARINDA - SUHUD, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2018)
Samarinda City is a city that has high transportation activities and has a high level of development. If this condition is not supported by an increase in transportation performance, it will cause traffic congestion problems. One of the roads that has a large role in the city of Samarinda is at the intersection of Jalan Ir. H. Juanda - Jalan A. Wahab Sahranie - Jalan Kadrie Oening - and Jalan Letjend Suprapto. The level of traffic congestion and traffic is quite large because it is one of the main roads in the city that divides the blood of the center of activities in Samarinda on this basis, so research is conducted on the level of service through the road section Ir. H. Juanda - street A. Wahab Sahranie - Kadrie Oening road - and Jalan Letjend Suprapto in samarinda against all vehicles without fly over               As for the Evaluation of the Level of Road Service Ir. H. Juanda - Jalan A. Wahab Sahranie - Jalan Kadrie Oening - and Jalan Letjend Suprapto use the Indonesian Road Capacity Manual (MKJI'1997), which is described based on Form UR-1 in the form of general and Geometric road conditions, UR-2 in the form of data Follow-up input is Traffic Flow and Composition and Side Obstacle, UR-3 in the form of Analysis of Speed of free flow of light vehicles, capacity and speed of light vehicles.            In the study of Ealuation, the level of service is Jl. Ir. H. Juanda - Jl. Kadrie Oening - Jl. H. A.W. Syahrani - and Jl. Letjend Suprapto Jalan conducted a survey 12 hours for 4 weeks, the first week on Jl. Ir. H. Juanda, the second week on Jl. Kadrie Oening, third week on Jl. H. A.W. Syahrani and the fourth week on Jl. Letjend Suprapto, this survey was conducted at 07.00-1800. After calculating the available data, at Air Black IV intersection, the service level is at the C level, which means the current zone is stable, the driver is limited to choosing speed